Religion and entrepreneurship - David B. Audretsch; Werner Boente; Jagannadha Pawan Tamvada (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
While considerable concern has emerged about the impact of religion on economic development, little is actually known about how religion impacts the decision making of individuals. This paper examines the influence of religion on the decision for people to become an entrepreneur. Based on a large-scale data set of nearly ninety thousand workers in India, this paper finds that religion shapes the entrepreneurial decision. In particular, some religions, such as Islam and Christianity, are found to be conducive to entrepreneurship, while others, such as Hinduism, inhibit entrepreneurship. In addition, the caste system is found to influence the propensity to become an entrepreneur. Individuals belonging to a backward caste exhibit a lower propensity to become an entrepreneur. Thus, the empirical evidence suggests that both religion and the tradition of the caste system influence entrepreneurship, suggesting a link between religion and economic behavior.
Keywords: L26; Z12; 330; entrepreneurship; religion; caste-system; India; Berufswahl; Entscheidung; Unternehmer; Religion; Indien